Skin whitening agents: medicinal chemistry perspective of tyrosinase inhibitors - Thanigaimalai Pillaiyar; Manoj Manickam; Vigneshwaran Namasivayam (Taylor & Francis Group, 2017)
Melanogenesis is a process to synthesize melanin, which is a primary responsible for the pigmentation of human skin, eye and hair. Although numerous enzymatic catalyzed and chemical reactions are involved in melanogenesis process, the enzymes such as tyrosinase and tyrosinase-related protein-1 (TRP-1) and TRP-2 played a major role in melanin synthesis. Specifically, tyrosinase is a key enzyme, which catalyzes a rate-limiting step of the melanin synthesis, and the downregulation of tyrosinase is the most prominent approach for the development of melanogenesis inhibitors. Therefore, numerous inhibitors that target tyrosinase have been developed in recent years. The review focuses on the recent discovery of tyrosinase inhibitors that are directly involved in the inhibition of tyrosinase catalytic activity and functionality from all sources, including laboratory synthetic methods, natural products, virtual screening and structure-based molecular docking studies.